The New Method in Calculating Columns and Beams Dimensions That Meets Requirements of The Strong Column-Weak Beam and Non-Soft Story - Livian Teddy; Gagoek Hardiman; N. Nuroji; Sri Tudjono (Journal of Architectural Design and Urbanism, 2019)
Situated at an earthquake prone area, buildings planning in Indonesia must implement earthquake resistant building principles. One of these principles is determining dimensions of columns and beams in the process of architectural designing.This act eventually affects the behaviour of the strong column-weak beam and the probability of bending failure due to soft story. At present time, there are no simple rules architects can use in calculating the dimensions of beams and columns that meet the criteria for strong column-weak beam and non-soft story. This paper is an effort to provide an input to the architects in designing the dimensions of the columns and beams. This research is a review result of three theories namely: 1). The theory of columns and beams preliminary design, 2). The theory of the strong column-weak beam concept, and 3). The theory of soft story and column slenderness. Those theories were then synthesized into a spreadsheet. To meet the criteria for strong column-weak beam and non-soft story, the following procedures must be done : 1). Determine the columns’ dimensions according to 0.15% of the columns’ cumulative tributary area, 2). Determine the beams’ dimensions according to 1/12 of the beams’ span and the beams’ plastic modulus, 3). Determine the columns’ dimensions and the columns’plastic modulus, 4). Determine the columns’ height based on the column slenderness criteria, and 5). Compare the columns plastic modulus and the beams plastic modulus and check whether they meet the criteria “the columns’plastic modulus ≥ 1.2 * the beams’ plastic modulus”.